History vs women the defiant lives that they don't want you to know - Sarkeesian, Anita 1983-; Adams, Ebony (Feiwel and Friends, 2018)
"Looking through the ages and across the globe, [the authors] have reclaimed the stories of twenty-five remarkable women who dared to defy history and change the world around them. From Mongolian wrestlers to Chinese pirates, Native American ballerinas to Egyptian scientists, Japanese novelists to British Prime Ministers, [this book] will reframe the history that you thought you knew"--Provided by publisher